Scalable and Purification-Free Synthesis of a Myristoylated Fluorogenic Sirtuin Substrate - Galleano, Iacopo; Nielsen, John; Madsen, Andreas S.; Olsen, Christian A. (Synlett, 2017)
Sirtuins are NAD+-dependent deacylases involved in the regulation of fundamental cellular processes in both normal and diseased cells. Therefore, the development of selective inhibitors for this class of enzymes is of great interest. Herein, we report an optimized synthesis of Ac-ETDK(myristoyl)-AMC, a sirtuin 2 substrate that can be used to profile inhibitors in fluorescence-based assays. The presented synthesis is scalable and does not involve chromatographic purification, making this substrate readily available in few steps.
Keywords: sirtuins; enzyme substrates; purification-free synthesis; posttranslational modifications; deacylases; SIRT2